Pitfalls of hypervisibility in the digital age - Beleli, Iara (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2022)
This article proposes a reflection on the search for partners on websites and on Tinder. The research focused on women, between 30 and 45 years old, who seek partners through these means. They all have higher education, live in the city of São Paulo and the vast majority declare themselves as middle class, “white” and heterosexual. The guiding question for this work is whether and how the use of new communication technologies has changed the search for partners, paying particular attention to the filters that make a candidate eligible. Those filters articulate differences of gender, race, location. Add to that the "things" that make up the image - furniture, room size, clothing, etc., so that goods and consumption are strategically intertwined not only to present themselves to the other, but also as a form of recognition. Social.